WOMEN’S IMAGES IN KARONESE SI BERU DAYANG FOLKLORE: CULTURAL ASPECTS - Emma Marsella; Dian Marisha Putri; Muhammad Ali Pawiro (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2022)
The Si Beru Dayang folklore is one of the cultural heritages in North Sumatra, and it belongs to Karonese society. Such folklore is believed to entertain the Karonese who still retell it to young generation according to its function since it contains local wisdom. This research is aimed at discussing women’s images seen from the perspective of cultural aspects. Qualitative descriptive methods and interviews were used in this research. The data collection was obtained from recording and from informants’ oral responses when they were invited during interviews; data was discussed from the domains of sociology of literature and from cultural aspects. The sociology of literature was focused on a number of concepts of women’s images in the folklore. The results show that women are portrayed as anak beru (wife taker/daughter), ndehara (wife), and sirukatnakan (rice dipper) as symbols of origin of rice in Karo land, and as women in the merdang traditional ritual.